Nanoscale friction characteristics of layered-structure materials in dry and wet environments - Sattari Baboukani, Behnoosh; Nalam, Prathima C.; Komvopoulos, Kyriakos (Frontiers in Mechanical Engineering, 2022)
Bulk layered materials, such as graphite and molybdenum disulfide, have long been used as solid lubricants in various industrial applications. The weak interlayer van der Waals interactions in these materials generate a low shear slip-plane, which reduces the interfacial friction. The cumulative trends toward device miniaturization have increased the need for basic knowledge of the nanoscale friction of contact-mode devices containing layered materials. Further, the decomposition and degradation of bulk layered solids subjected to shear forces are detrimental to their lubricating characteristics. Layered-structure materials, such as graphene, hexagonal boron nitride, and MXenes consisting of single or few atomic layers, behave as a new class of lubricious substances when deposited at a sliding interface. The exceptional mechanical strength, thermal conductivity, electronic properties, large theoretical specific area, and chemical inertness of these materials make them ideal antifriction materials for continuous sliding interfaces, especially when operated at elevated temperatures. However, accurate and reliable prediction of the frictional behavior of layered-structure materials is challenging due to the complex physicochemical transformations encountered under tribostress. The presence of a liquid in the vicinity of a surface in wet-environment applications further complicates the lubrication behavior of layered-structure materials. Insight into the origins of interfacial friction and adhesion due to localized contact interactions can be accomplished by atomic-level experimental techniques and computational methods, such as atomic force microscopy (AFM) in combination with molecular dynamics (MD) and density functional theory (DFT). The objective of this review article is threefold. First, the relationship between friction and potential energy surface is examined for different layered-structure material systems, and the parameters that mainly affect the energy corrugation are interpreted in the context of reported results. Second, the atomic-scale friction mechanisms of layered-structure materials in dry or vacuum environments are discussed in light of experimental and theoretical findings, focusing on the most crucial frictional energy dissipation mechanisms. Third, the complex mechanisms affecting the nanosccale friction of layered-structure materials incorporated in liquid media are introduced for ionic, polar, and non-polar solutions.